Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006539.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection for treatment of glaucoma in adults

Abstract: Background Glaucoma is a heterogeneous group of conditions involving progressive damage to the optic nerve, deterioration of retinal ganglion cells and ultimately visual field loss. It is a leading cause of blindness worldwide. Open angle glaucoma (OAG), the commonest form of glaucoma, is a chronic condition that may or may not present with increased intraocular pressure (IOP). Neuroprotection for glaucoma refers to any intervention intended to prevent optic nerve damage or cell death. The treatment can target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 71 publications
0
57
0
5
Order By: Relevance
“…Although some smaller-scale studies have indicated that this may translate into visual field preservation, there is currently no sufficient evidence for a clinically meaningful neuroprotective effect, a conclusion that has recently also been drawn by a Cochrane Review on this subject. 95 Neuroprotection studies are difficult to perform for many reasons mentioned later in this review. One additional concern when comparing IOP-lowering drugs with regard to their visual field preserving effect arrives from IOP measurement itself, because lowering IOP at a certain time point does not necessarily result in a comparable 24 h IOP profile.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Although some smaller-scale studies have indicated that this may translate into visual field preservation, there is currently no sufficient evidence for a clinically meaningful neuroprotective effect, a conclusion that has recently also been drawn by a Cochrane Review on this subject. 95 Neuroprotection studies are difficult to perform for many reasons mentioned later in this review. One additional concern when comparing IOP-lowering drugs with regard to their visual field preserving effect arrives from IOP measurement itself, because lowering IOP at a certain time point does not necessarily result in a comparable 24 h IOP profile.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…This Low-pressure Glaucoma Treatment Study (LoGTS) demonstrated a lower rate of progression of visual field loss in subjects treated with brimonidine compared to timolol, a beta-adrenergic antagonist which is not neuroprotective, but which lowered intraocular pressure in this study to a similar extent as brimonidine. This small study was critiqued for differential dropout, changes in the statistical analysis, and other issues (Cordeiro and Levin 2011;Sena and Lindsley 2013).…”
Section: Historical Summary Of Neuroprotection In Glaucomamentioning
confidence: 99%
“…It is a progressive disease affecting people above 40 years, optic nerve changes are the main features, intraocular pressure (IOP) is the famous measurable risk factor for POAG, but some cases with the reduction of their IOP either by medical or surgical treatment does not stop the progression of the disease. So, other factors as lack of neurological protection for ganglion cells in the retina and cell apoptosis mechanisms may also play roles in progression of glaucoma [1] [2] [3]. Another factor may be incriminated in the process of POAG such as oxidative stress, other inflammatory factors and characteristic pattern of cell death by apoptosis [4].…”
Section: Introductionmentioning
confidence: 99%